2019
DOI: 10.3390/pharmaceutics11120663
|View full text |Cite
|
Sign up to set email alerts
|

Investigation to Explain Bioequivalence Failure in Pravastatin Immediate-Release Products

Abstract: The purpose of this work is to explore the predictive ability of the biopharmaceutics classification system (BCS) biowaiver based on the dissolution methods for two pravastatin test products, where one of them showed bioequivalence (BE) while the other test failed (non-bioequivalence, or NBE), and to explore the reasons for the BE failure. Experimental solubility and permeability data confirmed that pravastatin is a BCS class III compound. The permeability experiments confirmed that the NBE formulation signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…To select the concentrations of excipients to be tested, we took the data from our previous publications in which we evaluated pharmaceutical formulations from bioequivalence studies with some in vivo failures. The composition of tests (Bioequivalent, BE or failing BE tests, i.e., Non-BE) and reference products were compared, and those excipients from the Non-BE formulations that were not contained in the reference or BE ones were selected (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…To select the concentrations of excipients to be tested, we took the data from our previous publications in which we evaluated pharmaceutical formulations from bioequivalence studies with some in vivo failures. The composition of tests (Bioequivalent, BE or failing BE tests, i.e., Non-BE) and reference products were compared, and those excipients from the Non-BE formulations that were not contained in the reference or BE ones were selected (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…However in the presence of alkali media, the release rate was faster due to phosphate ions. 7,60 The release of PVS from F5 NPs was a biphasic, initial burst release at the first 2 h was followed by a controlled release phase till 4 h. This is may be due to the spontaneous partitioning of PVS into the dissolution medium upon addition of the freeze-dried F5 NPs due to its higher water solubility besides the presence of a quantity on the surface of PLGA-NPs explaining the burst release observed. 61 The controlled release phase could be attributed to the drug entrapped in the NPs that could be released in a regulated manner.…”
mentioning
confidence: 98%
“…The dissolution profile of PVS in acidic pH (Figure7A) lower than that in basic pH (Figure7B and C); this was attributed to PVS is weak acidic and its pKa value is 4.2. However in the presence of alkali media, the release rate was faster due to phosphate ions 7,60. The release of PVS from F5 NPs was a biphasic, initial burst release at the first 2 h was followed by a controlled release phase till 4 h. This is may be due to the spontaneous partitioning of PVS into the dissolution medium upon addition of the freeze-dried F5 NPs due to its higher water solubility besides the presence of a quantity on the surface of PLGA-NPs explaining the burst release observed 61.…”
mentioning
confidence: 99%
“…This tool allowed for the development of a model to predict Papp in Caco-2 cells permeability for drugs that are transported across the intestinal membrane not only in passive diffusion but also in transporter - mediated active transport. The group of Bermejo and González-Álvarez demonstrated that in vitro permeability studies in Caco-2 can be used to compare formulation performance and even to explain bioequivalence failures associated with excipient effect on the intestinal membrane [ 34 ]. In this study, Ruiz-Picazo et al showed that permeability differences in rat vs. Caco-2 cells of pravastatin formulations (a BCS class III compound) can explain the bioequivalence failure and the higher C max due to excipient effects on the intestinal membrane in the nonequivalent formulation.…”
mentioning
confidence: 99%
“…In this study, Ruiz-Picazo et al showed that permeability differences in rat vs. Caco-2 cells of pravastatin formulations (a BCS class III compound) can explain the bioequivalence failure and the higher C max due to excipient effects on the intestinal membrane in the nonequivalent formulation. In the same article, the authors demonstrated non-similar dissolution profiles with USP apparatus and the relevance of using 500 mL instead of 900 mL [ 34 ]. A great research effort is focused on the development of new dissolution systems, mono- and multi-compartmental dynamics models.…”
mentioning
confidence: 99%